Circadian Rhythms in the CNS and Peripheral Clock Disorders: Function of Clock Genes: Influence of Medication for Bronchial Asthma on Circadian Gene - Naoto Burioka; Yasushi Fukuoka; Miyako Takata; Masahiro Endo; Masanori Miyata; Hiroki Chikumi; Katsuyuki Tomita; Masahiro Kodani; Hirokazu Touge; Kenichi Takeda; Takashi Sumikawa; Kousuke Yamaguchi; et al. (Elsevier, 2007)
Bronchial asthma is a chronic inflammatory disorder of the airways, in which inflammation causes bronchial hyper-responsiveness and flow limitation in the presence of various stimuli. Pulmonary function in asthmatic patients frequently deteriorates between midnight and early morning, which has suggested a role for chronotherapy. Although relationships between bronchial asthma and the function of clock genes remain unclear, some medications given for asthma such as glucocorticoids or β2-adrenoceptor agonists may influence clock genes in vivo. In our studies of clock gene mRNA expressions in human bronchial epithelial cells in vitro and peripheral blood cells in vivo, we demonstrated that glucocorticoid or β2-adrenoceptor agonist treatment strongly induced human Per1 mRNA expression both in vitro and in vivo. Human peripheral blood cells provide a useful indication of peripheral clock gene mRNA expression in vivo. Keywords:: β2-adrenoceptor agonist, cAMP, clock gene, glucocorticoid, Per1